Paper structures: Case studies - Latka, Jerzy F. (A+BE | Architecture and the Built Environment, 2018)
The examples of paper architecture presented in this chapter show the wide variety of materials and compositions used. The chosen examples are divided into two sections. The first section, entitled ‘The History of Paper in Architecture,’ embraces the projects realised from the late nineteenth century to the late 1980s. The examples provided in the ‘Case Studies’ section were assessed more thoroughly for their function, structural system, usable area, used material, connections and details of the structure (foundation, walls, roof), impregnation and lifespan. The chosen projects represent the most interesting solutions as far as structure and use of materials are concerned. Each of the examples described in this section presented an element of novelty in the world of paper architecture.